Chronic respiratory diseases other than asthma in children: the COVID-19 tsunami - Maria Di Cicco; Maria Giulia Tozzi; Vincenzo Ragazzo; Diego Peroni; Ahmad Kantar (BMC, 2021)
Abstract Coronavirus disease 2019 (COVID-19) affects all components of the respiratory system, including the neuromuscular breathing apparatus, conducting and respiratory airways, pulmonary vascular endothelium, and pulmonary blood flow. In contrast to other respiratory viruses, children have less severe symptoms when infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A minority of children experience a post-infectious inflammatory syndrome, the pathology and long-term outcomes of which are poorly understood. The reason for the lower burden of symptomatic disease in children is not yet clear, but several pathophysiological characteristics are postulated. The SARS-CoV-2 pandemic has brought distinct challenges to the care of children globally. Proper recommendations have been proposed for a range of non-asthmatic respiratory disorders in children, including primary ciliary dyskinesia and cystic fibrosis. These recommendations involve the continuation of the treatment during this period and ways to maintain stability. School closures, loss of follow-up visit attendance, and loss of other protective systems for children are the indirect outcomes of measures to mitigate the COVID-19 pandemic. Moreover, COVID-19 has reshaped the delivery of respiratory care in children, with non-urgent and elective procedures being postponed, and distancing imperatives have led to rapid scaling of telemedicine. The pandemic has seen an unprecedented reorientation in clinical trial research towards COVID-19 and a disruption in other trials worldwide, which will have long-lasting effects on medical science. In this narrative review, we sought to outline the most recent findings on the direct and indirect effects of SARS-CoV-2 pandemic on pediatric respiratory chronic diseases other than asthma, by critically revising the most recent literature on the subject.